2019
DOI: 10.1029/2018jd030064
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Dioxide Modifies Aerosol Particle Formation and Growth by Ozonolysis of Monoterpenes and Isoprene

Abstract: The effect of sulfur dioxide on particle formation and growth by ozonolysis of three monoterpenes (α‐pinene, β‐pinene, and limonene) and isoprene was investigated in the presence of monodisperse ammonium sulfate seed particles and an OH scavenger in a flow tube under dry conditions. Without sulfur dioxide, new particle formation was not observed, and seed particle growth was consistent with condensation of low‐volatility oxidation products produced from each organic precursor. With sulfur dioxide, new particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…Previous studies have reported that the BVOC emissions over the NCP have increased in the last decade because of the afforestation and accelerating global warming (Stavrakou et al, 2014;Ma et al, 2019). During our observations, the total VOCs (including C 2 -C 10 ) mixing ratios approached 16.1 ± 6.5 ppb in the 2018 spring campaign, which was almost double that (including C 4 -C 12 ) in the June 2006 campaign (Mao et al, 2009; no data from the spring 2007 cam-Figure 6.…”
Section: Potential Contribution To Ccn Production From the Npf Eventssupporting
confidence: 51%
“…Previous studies have reported that the BVOC emissions over the NCP have increased in the last decade because of the afforestation and accelerating global warming (Stavrakou et al, 2014;Ma et al, 2019). During our observations, the total VOCs (including C 2 -C 10 ) mixing ratios approached 16.1 ± 6.5 ppb in the 2018 spring campaign, which was almost double that (including C 4 -C 12 ) in the June 2006 campaign (Mao et al, 2009; no data from the spring 2007 cam-Figure 6.…”
Section: Potential Contribution To Ccn Production From the Npf Eventssupporting
confidence: 51%
“…For example, intense bursts of nuclei mode particles were observed in rural forests in Michigan and Alabama with elevated SO 2 concentrations (at ppbv), while NPF did not occur even during the daytime under low or moderate SO 2 concentrations (at sub-ppbv; Kanawade et al, 2011;Lee et al, 2016). It was hypothesized that some heterogeneous oxidation processes can produce sulfuric acid on small particles , similarly to those found on cloud and fog droplets (Finlayson-Pitts & Pitts, 2000;Seinfeld & Pandis, 2016) and acidic aerosol particles (Hung & Hoffmann, 2015;Stangl et al, 2019).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 96%
“…At present, there is still no clear evidence from atmospheric observations that demonstrates "causal effects" of temperature and RH on NPF (Lee et al, 2019). Recent CLOUD studies have shown that oxygenated organics formed from biogenic volatile organic compounds (BVOCs) can grow newly nucleated particles in a wide range of tropospheric temperatures (Stolzenburg et al, 2018). This is because gas-phase autooxidation reactions involved in the formation of highly oxidized molecules (HOMs) usually have strong temperature dependencies, with higher reaction rates at higher temperatures (Frege et al, 2018), whereas nucleation is favored at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%